School Strategic Planning Utilizing VMTS Framework: A Case Study at SMP Negeri 1 Kedungwuni Pekalongan - Ari Sasongko, Supomo; Setiyo Budi, Sigit; Novi Susanti, Khelly; Erviana, Susi; Nyoman, Ngurah Ayu (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study examines the implementation of strategic planning based on the VMTS model (Vision, Mission, Goals, and Objectives) at SMP Negeri 1 Kedungwuni, Pekalongan Regency. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis. The results show that although the school has formally established its vision, mission, goals, and objectives, the dissemination and understanding among staff and stakeholders remain uneven, leading to suboptimal implementation. Challenges such as limited budget, human resources, and the absence of systematic monitoring and evaluation hinder the execution of strategic programs. Additionally, stakeholder participation needs improvement to foster stronger ownership and commitment. The study recommends enhancing communication and socialization of strategic plans, increasing stakeholder involvement, establishing structured monitoring and evaluation systems, and optimizing resource management. These measures are vital to support the sustainable improvement of educational quality at SMP Negeri 1 Kedungwuni.